"I was Excited by the Idea of a Project that Focuses on those Unasked Questions" Co‐Producing Disability Research with Disabled Young People. (7th December 2018) - Liddiard, Kirsty; Runswick‐Cole, Katherine; Goodley, Dan; Whitney, Sally; Vogelmann, Emma; Watts MBE, Lucy
Abstract : In this article, we detail the politics and practicalities of co‐produced disability research with disabled young people with life‐limiting and life‐threatening impairments. We centre an ESRC‐funded arts‐informed co‐produced research project that has brought together a Co‐Researcher Collective of disabled young people. Co‐production is an established approach; however, our co‐researchers have led us to develop inclusive research practices that engage with online social research methods in innovative ways. As we detail our experiences, we aim to encourage disability studies researchers and others to adopt virtual environments when researching with and for the lives of disabled people.